MUZÍKA SABAǴÍNDA «SIMFONIYALÍQ ORKESTR» TEMASÍN OQÍTÍWDA INTERAKTIV METODLARDAN PAYDALANÍW - Axetova, G.J. (SCIENCE and SOCIETY, 2025)
This article discusses the use of interactive methods in teaching music in comprehensive schools. The topic of "Symphony Orchestra" was chosen as the object of study. The following interactive methods were used: "Passport," "Zig-Zag," and "Scrabble."